Airway remodelling rather than cellular infiltration characterizes both type2 cytokine biomarker‐high and ‐low severe asthma. Issue 10 (25th May 2022) - Khalfaoui, Latifa; Symon, Fiona A.; Couillard, Simon; Hargadon, Beverley; Chaudhuri, Rekha; Bicknell, Steve; Mansur, Adel H.; Shrimanker, Rahul; Hinks, Timothy S. C.; Pavord, Ian D.; Fowler, Stephen J.; Brown, Vanessa; et al.
Abstract: Background: The most recognizable phenotype of severe asthma comprises people who are blood eosinophil and FeNO‐high, driven by type 2 (T2) cytokine biology, which responds to targeted biological therapies. However, in many people with severe asthma, these T2 biomarkers are suppressed but poorly controlled asthma persists. The mechanisms driving asthma in the absence of T2 biology are poorly understood. Objectives: To explore airway pathology in T2 biomarker‐high and ‐low severe asthma. Methods: T2 biomarker‐high severe asthma (T2‐high, n  = 17) was compared with biomarker‐intermediate (T2‐intermediate, n  = 21) and biomarker‐low (T2‐low, n  = 20) severe asthma and healthy controls ( n  = 28). Bronchoscopy samples were processed for immunohistochemistry, and sputum for cytokines, PGD2 and LTE4 measurements. Results: Tissue eosinophil, neutrophil and mast cell counts were similar across severe asthma phenotypes and not increased when compared to healthy controls. In contrast, the remodelling features of airway smooth muscle mass and MUC5AC expression were increased in all asthma groups compared with health, but similar across asthma subgroups. Submucosal glands were increased in T2‐intermediate and T2‐low asthma. In spite of similar tissue cellular inflammation, sputum IL‐4, IL‐5 and CCL26 were increased in T2‐high versus T2‐low asthma, and several further T2‐associated cytokines, PGD2 and LTE4, were increased in T2‐high and T2‐intermediate asthma compared with healthy controls. Conclusions: Eosinophilic tissue inflammation within proximal airways is suppressed in T2 biomarker‐high and T2‐low severe asthma, but inflammatory and structural cell activation is present, with sputum T2‐associated cytokines highest in T2 biomarker‐high patients. Airway remodelling persists and may be important for residual disease expression beyond eosinophilic exacerbations. Registered at ClincialTrials.gov : NCT02883530. Abstract : People with T2‐high and T2‐low severe asthma, and healthy controls, have similar airway tissue inflammatory cells counts, but sputum T2 cytokines persist in T2‐high asthma, likely driving eosinophilic exacerbations through recruitment of blood eosinophils. In both T2‐high and T2‐low asthma, extensive airway wall remodelling is present and likely contributes to residual disease expression beyond T2 exacerbations. As bronchoconstriction and mucus plugging are the predominant causes of airflow obstruction driving asthma symptoms, exacerbations and death, the factors that sustain these abnormal pathological features should be a priority for future research and drug development for severe asthma.Abbreviations: CCL, C‐C motif chemokine ligand; Eos, eosinophil; FeNO, fraction of exhaled nitric oxide; GC, goblet cell expressing MUC5AC; IL, interleukin; LTE4, leukotriene E4; MC, mast cell; Neu, neutrophil; T2, type2 cytokine; PGD2, prostaglandin D2; TSLP, thymic stromal lymphopoietin